Internal auditors' characteristics and corporate governance on the performance of internal auditors in Thailand Public Limited Company - Narkchai, Sutana (2015)
The issue of performance of internal auditors is important since Thailand was also affected by the accounting scandals. The expanded scope in the definition of internal auditing and new regulatory requirements such as the Sarbanes-Oxley Act has increased the demands on internal auditing. This study was conducted to examine the factors that influence the internal auditors' characteristics and corporate governance on the performance of internal auditors in Thailand public limited companies. To achieve this objective, seven hypotheses were formulated based on previous studies and the agency theory. Survey questionnaires were sent to the Chief Audit Executives to determine their to effectiveness on their performance based on the professional standards issued by the International Professional Practices Framework indicators. A total of 520 questionnaires were distributed, but only 146 were usable. The questionnaire was designed to collect information on internal auditors' characteristics and corporate governance factors. Internal auditors' characteristics were represented by demographic profile, regulation compliance awareness, adoption of internal auditing standards, audit professionalism and communication skills while corporate governance was represented by board of director and audit committee. Multiple regression was used to test the relationship between the variables. Three out of the seven variables which have affected the performance of internal auditors were audit professionalism, communication skills and audit committee. Demographic profile, regulation compliance awareness and adoption of internal auditing standards do not have significant influence on performance of internal auditors. The results of this study show that there is an implication on the practice low compliance, lack of awareness of standards and non-adoption of International Professional Practices Framework. This study serves as an important catalyst for further research and discussion in this area. More importantly, there is lack of research in Thailand concerning the relationship between internal audit functions with the performance of internal auditors.